The Heart of NavIC-Navigation with Indian Constellation - N. Bandi, Thejesh (Biology, Engineering, Medicine and Science Reports)
Global Navigation Satellite System (GNSS) has become indispensable for various applications worldwide. Regional navigation satellite systems cover the regions up to 1500 km2 providing the Positioning, Navigation, and Timing (PNT) solutions. Navigation with Indian Constellation (NavIC) is such a regional system, now having its own indigenously developed space atomic clock - the Indian Rubidium Atomic Frequency Standard (IRAFS) that was launched onboard NVS-01 providing services to the Indian subcontinent. This paper provides an overview of the successfully developed IRAFS technology and its performance capabilities meeting the stringent space clock requirements for NavIC, and provides directions for the future aspects that could improve the technology further.
Keywords: NavIC; GNSS; Rubidium; Atomic Clock; IRAFS; Satellite; Positioning; Navigation; Timing (PNT)